2013
DOI: 10.1002/hc.21128
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Study of NO2 Adsorption on C20 Fullerene

Abstract: Using different density functional theory methods, covalent functionalization of C20 fullerene with the NO2 molecule in terms of energy, geometry, and electronic properties was investigated. It was found that the molecule has strongly chemisorbed on the fullerene surface with Gibbs free energies in the range of −25.23 to −33.07 kcal/mol at the PBE level and −21.03 to −37.95 kcal/mol at the B3LYP level. The HOMO–LUMO gap of the fullerene has changed significantly upon the NO2 adsorption. The Fermi‐level energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 28 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…This parameter is a good measure to examine the solubility of molecules in polar solvents. Molecules with higher dipole moments have better solubility in water solvents and compounds with less bipolar moments have lower solubility in dipole solvents [30]. According to the results, after binding with fullerene the dipole moment except for I-Isomer, for other Isomers have increased.…”
Section: C1-o1 C1-o2 C1-o3 C1-o4 C1-n1 C1-n2 C1-n3mentioning
confidence: 88%
See 1 more Smart Citation
“…This parameter is a good measure to examine the solubility of molecules in polar solvents. Molecules with higher dipole moments have better solubility in water solvents and compounds with less bipolar moments have lower solubility in dipole solvents [30]. According to the results, after binding with fullerene the dipole moment except for I-Isomer, for other Isomers have increased.…”
Section: C1-o1 C1-o2 C1-o3 C1-o4 C1-n1 C1-n2 C1-n3mentioning
confidence: 88%
“…According to the results, after binding with fullerene the dipole moment except for I-Isomer, for other Isomers have increased. Therefore, fullerene derivatives with Cytarabine are more soluble in water solvent than pure drug without substitution [28][29][30].…”
Section: C1-o1 C1-o2 C1-o3 C1-o4 C1-n1 C1-n2 C1-n3mentioning
confidence: 99%
“…270 It was found that the molecule has strongly The possibility of the formation of endohedral complexes between NH 3 molecules and C 60 was investigated by using ab initio DFT calculations. The obtained results indicate that only one NH 3 molecule being incorporated inside the C 60 cage can form a stable complex.…”
Section: Nh 3 and No Xmentioning
confidence: 99%
“…So, it is very important to find a procedure to functionalise this nanoparticle. Recently, some papers have proposed a new approach to functionalise C 20 fullerene [18][19][20]. Achievements to functionalise and utilise C 60 fullerenes through 1,3-dipolar reactions [21,22] with 4-pyridine nitrile oxide [23] was a factor that motivated us to develop a general scheme that included the potential of an open [5,5] cycloaddition reaction of 4-pyridine nitrile oxide with C 18 NB (Scheme 1) which is a derivative of C 20 fullerenes [24][25][26].…”
Section: Introductionmentioning
confidence: 99%